Secure cross-domain communication mechanism for Web mashups - Jian-hua SUN; Zhi-rong LIU; Hao CHEN (Tongxin xuebao)
Many methods were used in cross-domain communication,whereas they were hardly to meet the security and high performance requirements.To this end,a secure cross-domain communication(SCDC)mechanism was proposed for Web mashups.It encapsulates content from different trust domains as secure components,achieves cross-domain communication with layered communication stack,and shares fine-grained objects by wrapping objects.SCDC mechanism supports secure cross-domain communication,shares objects between mashups and components without any browser modifications.Experiments show that the mechanism improves the communication efficiency more than five-fold,and only incurs limited overhead.